Adventure Tourism in Santo Domingo Province Based in an Educational Proposal - Quezada-Sarmiento, Pablo Alejandro; Armijos-Jaramillo A.M.; Chango-Cañaveral P.M.; Alejandra Longa-López R.; Salas–Álvarez W.T.; Pomboza-Tamaquiza P.P. (My University, 2024)
This research realizes the technical and economic feasibility of the creation and implementation of an ADVENTURE TOUR based in an educational proposal and suggests that “It involves carrying out a series of activities that are generally developed in these natural spaces or their proximities. Unlike other forms of recreation, tourism adventure offers an original opportunity in which the participants experience more and focus on overcoming challenges, achieving collateral effects such as mental strength and releasing stress in each of the activities carried out” (Martínez and Fernández in Gran Tour: Revista de Investigaciones Turísticas 3:51–68, 2011). It is an active process which includes various activities organized in the trip to natural and exotic places, accessible and with a risk that produces adrenaline when doing these extreme sports which takes place in Santo Domingo de Los Tsáchilas and contains the following proposal. The activities are developed in different places near to the city of Santo Domingo de Los Tsáchilas; tourism allows to connect the highland with the low land toward the coast, this document has important information from Santo Domingo de Los Tsáchilas with three proposals for offering different activities in this important province, close to Quito supported on educational proposal. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.
Keywords: Experience; Robotics; Technological trends; Technology; Tourism